Counter-terrorism community engagement: pitfalls and opportunities - Hartley, Jason (Routledge studies in countering violent extremism, 2021)
"This book offers insights into the building of trust in Muslim communities through community engagement in a climate of counter-terrorism. Police engagement with Muslim communities is complex with a history of distrust. This book first attempts to understand the role and implications of uncertainty on community engagement in Muslim communities, and then explores the cultural nuances associated with the demonstration of trustworthiness, and decisions to bestow trust. It further highlights the complexities and implications for Muslim leaders when trying to simultaneously engage police and appease their own communities; the book exposes community perceptions of an over-reaction by authorities that has moved suspicion from a handful of terrorists to the entire Muslim community, resulting in problematic community perceptions that Muslim communities are being targeted by police. The findings suggest that the intentionality of police is a highly significant consideration in trust negotiations, and reveals a number of cultural preferences considered critical to trust negotiations. The book further highlights opportunities to enhance the development of trust and avoid pitfalls that can be problematic to community engagement. The lessons learned seek to enhance the existing body of literature regarding strategies and resources to improve counter-terrorism community engagement with Muslim communities. This book will be of much interest to students of counter-terrorism, preventing violent extremism, deradicalization, and security studies"--